Meningkatkan Motivasi dan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila Menggunakan Media Spin Game - Anggarwati, Happy; Nuria Hasnah Anggraini, Nyimas; Chotimah, Umi (ASANKA : Journal of Social Science and Education, 2024)
This study aims to increase the motivation and learning outcomes of students in the Pancasila Education subject by using spin game media at SMPN 33 Palembang. The method used is Classroom Action Research which is carried out in two cycles. The subjects in this study were all students of class VII.6 SMPN 33 Palembang with a total of 30 students. The results of the research that has been done show an increase in motivation and learning outcomes of students after using spin game media in Pancasila Education subjects. This is evident from the results of student motivation in the pre-cycle showing 57.5%, increasing in cycle 1 to 68% and in cycle 2 increasing to 81.5% (very good motivation category). While the learning outcomes of students during the pre-cycle were only 10 students who achieved KKM (33.3%), during cycle 1 it increased, namely 22 students reached KKM (73.3%), and in cycle 2 all students succeeded in achieving KKM ( 100%).